Community Empowerment through the Oyster Mushroom Cultivation Program in Kragilan Village - Alaya Rizka Salisa; Alifa Nurul Mufiroh; Rahmat Lutfi Guefara; Wahyu Suhardiyono; Rina Manasickana; Nabila Kharitsah; Anas Muhotib; Muhammad Irham Zamzami; Alfikran Gumohung; Andre Mahendra Heru Kusuma; Muhamad Anggun Tri Subekti; Jihan Hanifah; Ngulya Nafisatun; Sukin Sukin; Tri Muryanti; Fika Mar'atussa'adah (CV. Dharma Samakta Edukhatulistiwa, 2026)
The community empowerment program through oyster mushroom cultivation in Kragilan Village was implemented as an effort to improve the skills, independence, and economic welfare of the community based on local potential. This program is part of the Community Service Lecture (KPM) activities of Al-Qur'an Science University. The method used is Participatory Action Research (PAR), which emphasizes the active involvement of the community in all stages of the activity, including planning, implementation, observation, and program evaluation. Data collection techniques were carried out through interviews, participatory observation, group discussions, and documentation. Community service activities included socialization, technical training in oyster mushroom cultivation (baglog production and shed maintenance), harvest assistance, and website-based financial management assistance. The results of the activities showed an increase in community knowledge and skills in oyster mushroom cultivation, increased participation and motivation for entrepreneurship, and a growing awareness of the importance of orderly and transparent business and financial management. In addition, this program had a social impact in the form of increased cooperation and collective responsibility, as well as an economic impact in the form of potential additional income for the community. This oyster mushroom cultivation program is considered effective as a means of community empowerment and has the potential to be developed sustainably with support from various parties.